Optimalisasi Supervisi Berjenjang Kelengkapan Dokumentasi Keperawatan - Reidha Fitri Nurbaeti; Tuti Afriani; Hanny Handiyani; Khairul Nasri; Sudaryati Sudaryati (Journal of Telenursing (JOTING), 2023)
This research aims to identify the optimization of the implementation of tiered supervision for the completeness of nursing documentation in inpatient rooms. The method used is a case study approach with interviews, document review, observation, and problem analysis using fishbone analysis. The research results show that all nursing managers can optimize the implementation of tiered supervision for the completeness of nursing documentation. Nursing managers can carry out routine maintenance of staff under them regarding the suitability of the diagnoses raised with subjective and objective data collected from the results of assessments carried out by nurses, proven by trials of implementing tiered supervision in three inpatient rooms with observational evaluations, and data obtained that there is an increase in the percentage of conformity of diagnoses. First nursing with subjective and objective data from 43.4% to 82.6%, and second diagnosis from 52.1% to 95.65%. The room is in the refreezing change stage where, after implementation or trial, the Nursing Services Department and the head of the room, along with the PPJA and PA, are trying to maintain its continuity and become an organizational culture in the hospital. The conclusion of the activities carried out during the socialization and mentoring process has provided changes in behavior and mindset for nurses in implementing tiered supervision for completeness of nursing documentation on a routine and scheduled schedule. Keywords: Nursing Documentation, Nurse Manager, Tiered Supervision